2000
DOI: 10.1152/jappl.2000.88.1.142
|View full text |Cite
|
Sign up to set email alerts
|

Afferent input from rat slow skeletal muscle inhibits bioassayable growth hormone release

Abstract: The release of a bioassayable form of growth hormone (BGH), distinct from growth hormone as measured by immunoassay (IGH), from the rat pituitary into the blood is differentially regulated by afferent input from fast and slow skeletal muscles. Specifically, activation of low-threshold fast muscle afferents for 15 min increased plasma BGH by 217 and 295% and decreased pituitary BGH by 68 and 45% in male and female rats, respectively. In contrast, activation of slow muscle afferents inhibited BGH release, decrea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

11
21
0

Year Published

2000
2000
2020
2020

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(32 citation statements)
references
References 28 publications
11
21
0
Order By: Relevance
“…A more likely cause is muscle proprioception, which promotes GH release more than lactate (20,21). Eccentric FERG actions may increase proprioception to yield a delayed, yet greater, GH release 30 minutes postexercise (21). Because the current study did not measure proprioception, this mechanism is speculative but deserves inquiry.…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…A more likely cause is muscle proprioception, which promotes GH release more than lactate (20,21). Eccentric FERG actions may increase proprioception to yield a delayed, yet greater, GH release 30 minutes postexercise (21). Because the current study did not measure proprioception, this mechanism is speculative but deserves inquiry.…”
Section: Discussionmentioning
confidence: 86%
“…Performance of both concentric and eccentric actions within a single workout, as done with the current CE3 protocol but not in prior acute studies (14,28,29), may impede GH release, though this is unproven. A more likely cause is muscle proprioception, which promotes GH release more than lactate (20,21). Eccentric FERG actions may increase proprioception to yield a delayed, yet greater, GH release 30 minutes postexercise (21).…”
Section: Discussionmentioning
confidence: 99%
“…When rats are subjected to metabolic challenges such as fasting or cold exposure, GH measured by immunoassay (IGH) is unchanged, whereas pituitary GH measured by tibial bioassay (BGH) decreases (6). Previous experiments in our and other laboratories have shown that BGH is a pituitaryderived, biologically active peptide, which exists in humans (10,18,19,20, unpublished observations), rats (5,6,12,13), cattle (7), and cats (unpublished observations).…”
mentioning
confidence: 73%
“…Whereas BGH is known to respond to metabolic perturbations (6), recent data indicate that stimulation of proprioceptive neuromuscular afferents may be an additional pathway through which BGH is regulated. Gosselink et al (12,13) recently showed rapid BGH release from the rat pituitary in response to a short bout of electrical stimulation (15 min or less) of lowthreshold axons of the promixal ends of severed tibial and peroneal nerves, which innervate predominantly fast muscles. Neither muscle-derived nor other metabolic factors appeared to be involved in facilitating BGH release under these conditions, because stimulating the distal ends of these cut nerves for the same amount of time had no effect on plasma or pituitary BGH concentrations (13).…”
mentioning
confidence: 99%
“…Repeated cycling trials with 1 h recovery in between produced similar lactate responses, but attenuated GH response in the second trial, leading the authors to conclude that proprioceptive feedback was a greater contributor to GH secretion than lactate (Stokes et al 2002). Gosselink et al (2000) documented GH responses through proprioceptive feedback through muscle spindles and Golgi tendon organs. Thus, proprioceptive feedback of a greater magnitude to relative loading versus absolute loading of ECC contractions may have contributed to the similar GH responses in the present study.…”
Section: Discussionmentioning
confidence: 99%